Zoochemical Composition of Selected Sea Stars Collected from the Coastal Waters of Carmen, Agusan Del Norte, Philippines - Walag, Angelo Mark P.; Rosario, Romeo M. Del; Canencia, Oliva P. (Asian Journal of Biological and Life Sciences, 2019)
The marine ecosystem is home to 34 of 36 phyla in the animal kingdom. It is for this reason that substantial amount of marine-derived natural products with potential medicinal and therapeutic applications have been described, isolated and characterized. Majority of the invertebrate phyla have been accounted for, but few studies have been made on Philippine invertebrates. The goal of this research is to determine the zoochemical composition selected sea stars collected from the coastal waters of Carmen, Agusan del Norte, Philippines. Standard methods were employed to determine the zoochemical composition of Linckia laevigata, Protoreaster nodosus and Acanthaster planci ground samples. All sea stars showed presence of alkaloids, flavonoids, saponins, triterpenoids and cardiac glycosides while no presence of coumarins and phenolics and tannins were detected. The presence of these zoochemicals in sea stars was confirmed by the available literature although differences were noted particularly on the absence of phenolics in this study. Based on this study, the selected stars appeared to be rich in saponins and steroids which are known to possess biological activity that could be used to develop drugs. The other metabolites can also be exploited in the developing marine-derived drugs. Further analyses can be done especially in isolating these compounds and structurally elucidating them. Moreover, the isolated metabolites can also be tested individually for its biological activities. It is also suggested that more studies be conducted on these organisms to further understand their biochemistry which can be utilized before they become endangered or more so, extinct.
Keywords: Alkaloids; Natural Products Chemistry; Phenolics; Saponins; Sea stars